Erythraeus (Parerythraeus) thomasi sp. nov. (Acari: Actinotrichida: Erythraeidae) from Finland, with a redefinition of Parerythraeus Southcott, 1946 stat. nov. as a subgenus and a key to species - Roland, Elżbieta; Gabryś, Grzegorz (Zootaxa, 2020)
Erythraeus (Parerythraeus) thomasi sp. nov. is described and illustrated based on specimens collected from Finland. Parerythraeus Southcott, 1946 stat. nov., previously synonymized with Erythraeus Latreille, 1806, is considered a subgenus of Erythraeus. Thirteen species, including E. (P.) thomasi, are included in this subgenus, and a differential diagnosis is provided for the 12 adequately described species. A key to all known species of Erythraeus (Parerythraeus) is also provided.